Erasing the Nation: The Historiography of African Nationalism in Conqueror South Africa. Issue 168 (1st September 2021) - Delport, Terblanche
Abstract: The story of conqueror South African historiography relies on the ebbs and flows of narrative clichés and tropes. The main narrative arcs relate to historiographies that frame the understanding and analysis of conqueror South Africa. These historiographies interpret history as forming part of an epistemological paradigm of conqueror South Africa: a historiography that does not question the ethical right to conquest. This article focuses on the interpretations of African Nationalism by proponents of the liberal and Marxist historiographic traditions and critiques the way in which these historiographies depict and characterise African Nationalism. This historical characterisation bears an influence in current political and social discourse in conqueror South Africa: African Nationalism is relegated to a misguided moment in history, something to be reflected upon from a distance, an irrelevant phase in the long walk to a multiracial and cosmopolitan South Africa.